The Role Of Sharia Economics In Community Empowerment And Poverty Alleviation - Andi Zakaria (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The sharia economy has become a significant alternative solution in resisting the challenges of community empowerment and poverty alleviation, especially in countries where the majority of the population is Muslim. This study aims to analyze the role of sharia economics in improving community welfare through zakat, infaq, alms, and waqf (ZISWAF) mechanisms, as well as the role of sharia financial institutions in supporting micro, small and medium enterprises (MSMEs). Departing from the background of increasingly complex socio-economic problems faced by modern society, sharia economics offers an ethics and social justice-based approach that not only focuses on profit, but also on common welfare. This study uses a qualitative descriptive method with a literature study approach and secondary data analysis from scientific journals, reports of Islamic financial institutions, and empirical data from sharia-based economic empowerment programs that have been implemented in several countries. The results of the study show that productive zakat and productive waqf have a significant contribution in reducing poverty rates by providing business capital and access to better social services. In addition, Islamic financial institutions such as Baitul Maal wat Tamwil (BMT) play an important role in providing access to financing to small business actors who are not These findings confirm that the sharia economy is not just a theoretical solution, but has also had a real impact in empowering society and encouraging inclusive economic growth. With synergy between the government, financial institutions, and the community, the sharia economy can be the main pillar in creating sustainable and equitable social welfare.